FACTORS AFFECTING PRODUCT QUALITY DURING THE STORAGE PERIOD OF FRUITS AND VEGETABLES - Mamatkulov Orifjon Odiljon ogli; Makhalikov Rozali Bakhtiyor ogli; Kholikov Muhriddin Bakhromjon ogli (Western European Studies, 2025)
The most important physiological process in the storage of fruits and vegetables is respiration . As a result of respiration, carbohydrates, acids, oils, and preservatives in the products are oxidized, which decompose into the final products - water and carbon dioxide, releasing a certain amount of energy in this process. By properly managing physiological and biochemical processes during storage, it is possible to preserve fruits and vegetables in good quality.
Keywords: fruit; vegetable; breath extraction; cooling